2022
DOI: 10.1186/s12935-022-02566-2
|View full text |Cite
|
Sign up to set email alerts
|

PTH2R is related to cell proliferation and migration in ovarian cancer: a multi-omics analysis of bioinformatics and experiments

Abstract: Background Ovarian cancer is a common gynecological disease and seriously endangers women's health. Currently, there is still a lack of effective molecular markers for the diagnosis and treatment of ovarian cancer. The present study aimed to investigate the molecular markers associated with ovarian cancer. Methods The molecular and gene related to ovarian cancer were extracted from GEO database and TCGA database by bioinformatics, and the related g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…In this study, a total of 957 DEGs were screened, including 478 up regulated genes and 479 down regulated genes. Nodin et al [41], Xiaowei et al [42], Xu et al [43] and Callahan et al [44] showed that DACH2, PTH2R, AJAP1 and HLA-DMB were associated with cancer. Johnston et al [45] and Mangano et al [46] reported that LRFN5 and SCN2A were important target genes of neurological and psychological problems.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a total of 957 DEGs were screened, including 478 up regulated genes and 479 down regulated genes. Nodin et al [41], Xiaowei et al [42], Xu et al [43] and Callahan et al [44] showed that DACH2, PTH2R, AJAP1 and HLA-DMB were associated with cancer. Johnston et al [45] and Mangano et al [46] reported that LRFN5 and SCN2A were important target genes of neurological and psychological problems.…”
Section: Discussionmentioning
confidence: 99%
“…KM survival curve analysis demonstrated that overexpression of KLHL14 was correlated with a significantly shorter OS in patients with OV. Moreover, bioinformatic analyses indicated that KLHL14 played an important role in the microenvironment and drug sensitivity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%